A Review of Important Activities and Studies 1966-67 - Planning Commission (Planning Commission, 1966)
The principal activity in which the Planning Commission was engaged during 1966-67 was the preparation of the Fourth Five Year Plan and the detailed Annual Plan for 1967-68, After its approval by the Cabinet, the Draft Outline of the Fourth Five Year Plan was placed before the National Development Council for consideration at its meeting held on 20th and 21st August, 1966. The Council give its general approval to the Draft Outline and to the approach and priorities indicated therein. The Council also considered the question of determination of principles of allocation of Central Assistance to States in the Fourth Five Year Plan and set up an ad hoc Committee to consider the matter in detail. The Committee met on September 2 and again on December 9, 1966. Some (schemes which had earlier been classified as Centrally Sponsored Schemas in the Draft Outline were by mutual agreement transferred to the State sector.
Government of India Planning Commission